Fill in the blanks to complete the polynomial equation that shows the subtraction of the second expression from the first and the resulting difference.

9x^2+_x +13
-2x^2+12x+_
_x^2+5x+2

1 answer

To complete the polynomial equation given, we need to find values for the blanks such that:

\[ (9x^2 + _x + 13) - (2x^2 + 12x + _) = _x^2 + 5x + 2 \]

Let's denote the missing terms with variables for clarity:

  1. Let the first blank in the first polynomial be \( a \).
  2. Let the second blank in the second polynomial be \( b \).
  3. Let the blank in the resulting polynomial be \( c \).

This gives us:

\[ (9x^2 + ax + 13) - (2x^2 + 12x + b) = cx^2 + 5x + 2 \]

Now, we distribute the negative sign through the second polynomial:

\[ 9x^2 + ax + 13 - 2x^2 - 12x - b = cx^2 + 5x + 2 \]

Combining like terms on the left side results in:

\[ (9x^2 - 2x^2) + (ax - 12x) + (13 - b) = cx^2 + 5x + 2 \]

This simplifies to:

\[ (7x^2 + (a - 12)x + (13 - b)) = cx^2 + 5x + 2 \]

From this equation, we can set up the following for the coefficients:

  1. From the \( x^2 \) terms: \( 7 = c \)
  2. From the \( x \) terms: \( a - 12 = 5 \)
  3. From the constant terms: \( 13 - b = 2 \)

Now we solve each of these equations:

  1. Since \( 7 = c \), we have \( c = 7 \).
  2. For \( a - 12 = 5 \): \[ a = 5 + 12 = 17 \]
  3. For \( 13 - b = 2 \): \[ b = 13 - 2 = 11 \]

Thus, we find:

  • The first blank (coefficient of \( x \) in the first polynomial) is \( 17 \).
  • The second blank (constant term of the second polynomial) is \( 11 \).
  • The blank in the resulting polynomial (coefficient of \( x^2 \)) is \( 7 \).

Putting it all together, the complete equation becomes:

\[ 9x^2 + 17x + 13 - (2x^2 + 12x + 11) = 7x^2 + 5x + 2 \]

In summary:

  • The first blank is 17.
  • The second blank is 11.
  • The third blank is 7.